1995
DOI: 10.1021/ac00118a011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Octane Numbers and Reid Vapor Pressure of Commercial Petroleum Fuels Using FT-Raman Spectroscopy and Partial Least-Squares Regression Analysis

Abstract: A Fourier transform Raman spectrometer was used to collect the Raman spectra of 208 commercial petroleum fuels. The individual motor and research octane numbers (MON and RON, respectively) were determined experimentally using the industry standard ASTM knock engine method. Partial least-squares regression analysis was used to build regression models which correlate the Raman spectra of 175 of the fuels with the experimentally determined values for MON, RON, and pump octane number (the average of MON and RON) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Raman is expected to evaluate the lysozyme concentration changes in vapour diffusion hanging drop method with and without LangmuirBlodgett nanotemplate. Raman spectra have previously been subjected to quantitative infrared partial least-squares (PLS) models with remarkable success [4]. The PLS model generated correlates the spectral region from 2700 to 3600 cm -1 with the concentration (g/ ml) of lysozyme.…”
Section: Introductionmentioning
confidence: 99%
“…Raman is expected to evaluate the lysozyme concentration changes in vapour diffusion hanging drop method with and without LangmuirBlodgett nanotemplate. Raman spectra have previously been subjected to quantitative infrared partial least-squares (PLS) models with remarkable success [4]. The PLS model generated correlates the spectral region from 2700 to 3600 cm -1 with the concentration (g/ ml) of lysozyme.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting spectrum is similar to both the spectrum of the .525 8C boiling residue and of highly ordered graphite. All three spectra exhibit a strong peak at 1600 cm 2 1 , while the clay tailings spectrum also exhibits a weak, broad peak at 1380 cm 21 . No peaks were observed under these conditions in the UV Raman spectrum of an Australian kaolinite, a control clay sample.…”
Section: Resultsmentioning
confidence: 98%
“…PLS is a multivariate regression method based on forming latent variables that maximize the covariance between the observed variables and the response variables [23] by emphasizing and utilizing the regions in the Raman spectrum that correlate mostly with product formation. By using PLS regression models built from Raman spectra, Cooper et al demonstrated accurate predictions of chemical and physical properties, including the octane number and vapor pressures of petrochemical solutions [24]. This was further demonstrated by Dearing et al who predicted physical properties of crude oil distillates when combining IR, Raman, and nuclear magnetic resonance (NMR) information into data-fused models [25].…”
Section: Introductionmentioning
confidence: 97%